Diagnosis and Management of Early Stages of ALD - Gratacós-Ginès, Jordi; Alvarado-Tapias, Edilmar; Martí-Aguado, David; López-Pelayo, Hugo; Bataller, Ramón; Pose, Elisa (Seminars in Liver Disease, 2025)
Early forms of alcohol-associated liver disease (ALD) include different stages in the progression of compensated liver disease ranging from steatosis to steatohepatitis and fibrosis. ALD has been classically diagnosed at advanced stages more frequently than other liver diseases. This fact probably contributed to the scarcity of studies on early forms of ALD. Recent studies have investigated the prevalence of early ALD in the general population and have described the natural history of alcohol-induced steatosis and fibrosis, which have been linked to worse prognosis compared with early stages of other chronic liver diseases. In addition, studies on screening and early diagnosis of ALD in at-risk populations have shown that these strategies allow early detection and intervention. Of note, up to 28% of the United States population has concurrent alcohol use and metabolic syndrome, and estimated prevalence of advanced fibrosis among heavy drinkers with metabolic syndrome has increased from 3% in the 1990s to more than 10% in the 2010s. Therefore, new challenges and treatment opportunities will emerge for patients with ALD. In this review, we provide an overview of the state of the art in early ALD, focusing on natural history, diagnosis, and management, and provide insights into future perspectives.
Keywords: screening; fibrosis; steatosis; metabolic; alcohol